At the Origins of Classical Opera : Carlo Goldoni and the «dramma Giocoso per Musica». - Rista, Pervinca. (Varia Musicologica Series, 2018)
Perhaps because of his stature and influence as a comic playwright, Goldoni has rarely been considered as an innovator in the musical sphere. This study aims to shed new light on his primary role in the evolution of Classical opera, and on the legacy of his innovations in the European musical tradition.